2021
DOI: 10.1016/j.tranon.2020.100901
|View full text |Cite
|
Sign up to set email alerts
|

A predictive signature for oxaliplatin and 5-fluorouracil based chemotherapy in locally advanced gastric cancer

Abstract: Adjuvant chemotherapy(AC) plays a substantial role in the treatment of locally advanced gastric cancer (LAGC), but the response remains poor. We aims to improve its efficacy in LAGC. Therefore, we identified the expression of eight genes closely associated with platinum and fluorouracil metabolism ( RRM1 , RRM2 , RRM2B , POLH , DUT , TYMS , TYMP , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…DUT RNA expression was also associated with shorter disease-free survival in colorectal cancer patients undergoing adjuvant chemotherapy with 5-FU (67). In gastric tumor patients, positive expression of DUT at the protein level was associated with high grade and younger age at diagnosis (68). Our study revealed for the first time the association of DUT expression with the presence of distant metastases, which are a sign of worse prognosis in EOC patients.…”
Section: Discussionsupporting
confidence: 52%
“…DUT RNA expression was also associated with shorter disease-free survival in colorectal cancer patients undergoing adjuvant chemotherapy with 5-FU (67). In gastric tumor patients, positive expression of DUT at the protein level was associated with high grade and younger age at diagnosis (68). Our study revealed for the first time the association of DUT expression with the presence of distant metastases, which are a sign of worse prognosis in EOC patients.…”
Section: Discussionsupporting
confidence: 52%
“…However, the underlying mechanism of how the genes impacted OS and PFS in a reverse pattern still needed to be further illuminated. Among the PFS-associated genes, AURKA [ 22 , 39 ], CDK1 [ 40 ], and RRM2 [ 12 ] had been validated correlating to the platinum response by experimental methods. These reports partially verified that identifying platinum-response indicators among stemness-associated genes according to mRNAsi was reliable and worthwhile.…”
Section: Discussionmentioning
confidence: 99%
“…The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were performed and visualized by clusterProfiler R package, enrichplot, and ggplot2 [ 12 ]. The candidate key genes were eventually selected according to the enriched pathways.…”
Section: Methodsmentioning
confidence: 99%
“…In the clinical setting, the AIO-FLOT4 study demonstrated that the replacement of cisplatin to oxaliplatin in combination with epirubicin to docetaxel, did show a higher rate of curative resection (84% versus77%, p=0.01), and prolonged OS [HR 0.77 (0.63-0.94), p=0.012] [19]. More recently, oxaliplatin-specific signatures based on tumor biology are rigorously sought after in gastric cancer [20]. In order to clarify these confusing understandings about neoadjuvant chemotherapy for resectable gastric cancer, it is necessary to plan a new study targeting the pure neoadjuvant population of Stage III patients with a regimen containing oxaliplatin instead of cisplatin, and also with the latest non-invasive radical D2 surgery.…”
Section: Discussionmentioning
confidence: 99%